Genetic analysis of inherited retinal diseases in indigenous Southern African populations - Roberts, Lisa Jane (Division of Human Genetics, 2017)
Background: Inherited retinal diseases (IRDs) constitute a group of clinically and genetically heterogeneous conditions which cause degeneration of retinal photoreceptor cells and result in visual impairment. Characterisation of the genetic basis of IRD is not only beneficial for the affected families, but also contributes towards understanding of the disease pathobiology. Investigations into the molecular basis of IRDs have been ongoing in South Africa (SA) for over 30 years, however the evaluation of reported genetic mutations has yielded low returns in certain populations. Indigenous southern Africans comprise a unique population group with distinct genetic diversity, providing a valuable resource for genetic discoveries; nonetheless, this population remains largely underrepresented in genomic studies. The aim of this investigation was to characterise the underlying genetic mutations in a cohort of indigenous African IRD patients. Methods: The IRD registry in the Division of Human Genetics (University of Cape Town) was reviewed for causative mutations. Subsequently, upon identifying a mutation underlying Usher Syndrome in two indigenous African patients, an assay was designed to screen for this mutation in probands with different IRDs (n=170) and controls (n=51), and haplotype analysis was performed on mutation-positive individuals. The registry review additionally served to identify a suitable cohort for the application of next generation sequencing (NGS) technology. Whole exome sequencing (WES) was performed on genomic DNA samples from 56 individuals from 16 families. The WES data analysis strategy involved prioritisation of variants in reported and candidate IRD genes. Rare, co-segregating, pathogenic, exonic or splice variants were validated by Sanger sequencing. Custom TaqMan assays were designed to screen seven mutations, identified by WES, in 193 unrelated indigenous African probands with IRDs. Results: A homozygous founder mutation, c.6377delC in MYO7A, was identified in 43% of the indigenous African patients with Usher syndrome, which is the most common cause of deaf-blindness. Targeted WES data analysis of all known IRD genes resulted in identification of the underlying genetic defects in six distinct genes (RHO, PRPF3, PRPF31, ABCA4, CERKL, and PDE6B) in six families. Taqman screening revealed four additional probands with identical homozygous mutations in CERKL and PDE6B. An X-linked gene (RP2) mutation was subsequently identified in an affected family with semi-dominant retinitis pigmentosa. Supplementary analysis of the X-linked RPGR ORF15 mutation hotspot (not adequately covered by WES) identified two mutations in three families. A novel IRD gene, IDH3A, was found in one family by analysis of 22 putative candidate genes. The large number of variants in the remainder of the indigenous African exomes presented considerable challenges for identification of additional novel genes. Discussion: The results of this project have important implications for IRD molecular diagnostic services in SA. Using WES, a genetic diagnosis was obtained for ±73% of the indigenous African cohort, and ±70% of the causative mutations identified were novel. This outcome emphasises the superiority of NGS-based approaches over genotyping-based microarrays which screen for IRD mutations previously reported in other (mainly European-derived) populations. The unexpected identification of mutations in known X-linked genes in four families highlighted key considerations for IRD WES analysis. Cascade screening of mutations identified in this study, across larger cohorts of unrelated probands, revealed the genetic cause of IRD in additional cases and the number of indigenous African families in the registry with a genetic diagnosis was effectively doubled. Members of these families can now opt for diagnostic, carrier, or predictive testing of familial mutations. Finally, the information obtained from this research contributes towards a better understanding of the genetic architecture of IRDs in SA.